#followthebottle a mass media campaign on educating drivers about the anti-drunk driving law while addressing the increasing alcohol-related road crashes in Metro Manila - Soon, Mojahed Ariel T.; Ilagan, Joy (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
The levels of road crashes or accidents have been rising since 2012 by almost a hundred every year even with the recent implementation of the anti-drunk driving law in 2013. With the increasing sales of alcohol products and motor vehicles, drinking and driving of drivers became much more probable.

Along with that, preventive measures are not being developed to be more effective with the constantly changing offenders. The law enforcement is being ineffective and offenders are not even noticing them. Also, the content and delivery of the messages to prevent them are not being aligned with their current demographic and psychographic.

Alcohol effects are being underestimated because there is no exact guideline on how much to drink that would still be legal and safe. Instead, they constructed their own alcohol intake limits through their physical exhaustion and emotional states.

Drivers are not being educated with the blood alcohol concentration levels which resulted to the increased number of alcohol-related crashes.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Keywords: Traffic accidents; Drunk driving; Drunkenness (Crime) -- Law and legislation; Driving under influence of alcohol -- Effects